SCHOOL PRINCIPAL LEADERSHIP STYLE IN STRENGTHENING TEACHERS' WORK COMMITMENT IN ISLAMIC BOARDING SCHOOL-BASED INSTITUTIONS - Putri, Diah Maghfiroh Setiawan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research is a qualitative study that examines the role of the Principal's leadership style in increasing teacher work commitment at MTS Al-Islamiyah, an Islamic boarding school-based educational institution. Through an in-depth interview approach with School Principals, Senior Teachers, and Administrative Staff, this research explores the impact of participative leadership styles and Islamic boarding school values on teachers' work commitment. The research results highlight the importance of teacher participation in decision making as a key element in creating a supportive work environment. In addition, the harmony between Islamic boarding school values and leadership practices shows a positive impact in building strong work commitment among teachers. These findings contribute to an in-depth understanding of how the principal's leadership style interacts with the Islamic boarding school context in strengthening teachers' work commitment at the secondary education level. The conclusions of this research provide valuable insight into understanding how the leadership style of the Principal can be a determining factor in building teacher work commitment in Islamic boarding school-based educational institutions.